Geographical representation of editorial boards: a review in the field of library and information sciences - AKÇA, SÜMEYYE (My University, 2022)
© 2022, Akadémiai Kiadó, Budapest, Hungary.Diversity of editorial boards of academic journals has recently become one of the most frequently discussed topics in scientific communication. Diversity of editorial board is considered to be an important element affecting the journal, the field and the region in terms of the number and diversity of publications. In parallel with this increasing awareness in the academic circles, many studies on diversity in the literature at both the field and journal levels have been carried out. In this study, the editorial boards of academic journals in the field of Library and Information Sciences were analyzed in terms of accommodating geographical representation, and the effect of such diversity, if any, on the number of publications was investigated. The data set consisted of the journals in the mentioned field in the SCImago web page Journal Rankings. The analyzes were carried out based on 6126 persons registered to 212 journals, including chief editors. The findings of the study showed that 75.11% of all members of editorial boards were from North American and European countries. While Asian countries (Central and South Asia, and East and Southeast Asia) were represented by 13.16% in journals in the field of Library and Information Sciences. A linear correlation was found between the regions where the chief editors of the journals were registered and the assignments of the editorial boards. Moreover, a linear correlation was found between the editors of journals (chief editors and other editors assigned to boards) and the scientific outputs (citable documents, citations, and h-index) in terms of regional relationship. The consistency of the results with those of other studies in the literature clearly demonstrates a need for more transparent processes in academic publishing. A policy to ensure a fair and diverse representation in boards of journals features numerous multifaceted positive effects.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Kütüphanecilik; Bilgisayar Bilimleri; Mühendislik ve Teknoloji; Social Sciences and Humanities; Sociology; Library Sciences; Computer Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Sosyal Bilimler (SOC); Bilgisayar Bilimi; Sosyal Bilimler Genel; BİLGİ BİLİMİ VE KÜTÜPHANE BİLİMİ; Engineering, Computing & Technology (ENG); Social Sciences (SOC); COMPUTER SCIENCE; SOCIAL SCIENCES, GENERAL; INFORMATION SCIENCE & LIBRARY SCIENCE; Genel Sosyal Bilimler; Sosyal Bilimler ve Beşeri Bilimler; Bilgisayar Bilimi Uygulamaları; Fizik Bilimleri; Kütüphane ve Bilgi Bilimleri; General Social Sciences; Social Sciences & Humanities; Computer Science Applications; Physical Sciences; Library and Information Sciences; Academic journal; Diversity of editorial board; Geographical representation; Library and Information Sciences—LIS; SCImago